Eficiencia económica de los principales aeropuertos de Norteamérica, 2017-2022: un estudio comparativo a través de la envolvente de datos - Rodríguez Machorro, José Martín Gaspar (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The purpose of this research is to evaluate the economic efficiency of the main airports in North America during 2017-2022, by applying the Data Envelopment Analysis (DEA) methodology strengthened with a Bootstrap, Slacks and Benchmark Analysis. The process begins by specifying the technical efficiency, which is related to the ability to generate the maximum amount of production from a limited set of inputs. Then, the allocative efficiency is determined, which examines whether these inputs are being used in the best way based on their prices. By merging both, economic efficiency is determined, which provides a comprehensive evaluation of the system´s performance from an economic perspective. The airport of a community is an invaluable asset, since it promotes the trade, tourism, investment, the creation of companies and consequently the generation of more jobs. The airports analyzed are: a) from the United States, the international airports of Hartsfield-Jackson Atlanta, Dallas Forth-Worth and Denver Colorado; b) from Canada, the 3 busiest were selected: Toronto Pearson, Vancouver and Montréal's Pierre Elliot Trudeau airports; and, c) from Mexico, the 10 most active according to annual statistical reports of airport groups, such as the International Airports of Mexico City, Cancun, Guadalajara, Tijuana, Monterrey, Los Cabos, Puerto Vallarta, Guanajuato, Mérida and Culiacán. The results obtained show that in all the airports it is recommended to implement strategies to increase their economic performance. The peculiarity of this study lies in obtaining economic efficiency strengthened with bootstrapping for this industry particularly in Mexico, since there are no researches with these specific characteristics.

El propósito de este estudio es evaluar la eficiencia económica de los principales aeropuertos de América del Norte durante el período 2017-2022, aplicando la metodología Análisis Envolvente de Datos (DEA por sus siglas en inglés), robustecido con un Bootstrap, así como análisis de Slacks y Benchmarking competitivo. Se inicia precisando la eficiencia técnica que tiene que ver con la habilidad de generar la mayor cantidad de producción a partir de un conjunto limitado de insumos, después se determina la eficiencia asignativa que examina si estos insumos se están empleando de la mejor manera en función de sus precios y fusionando ambas se determina la eficiencia económica que proporciona una evaluación completa del desempeño del sistema desde un enfoque económico. El aeropuerto de una comunidad es un activo valioso, puesto que promueve los mercados de bienes y servicios, el sector turístico, tanto la inversión nacional como la internacional, la generación de compañías y por ende acelera la creación de más posiciones de trabajo. Los aeropuertos que se analizaron son: a) de Estados Unidos, los aeropuertos internacionales de Hartsfield-Jackson Atlanta, Dallas Forth-Worth y Denver Colorado; b) de Canadá, los de Toronto Pearson, Vancouver y Pierre Elliot Trudeau de Montreal; y, c) de México, los Aeropuertos Internacionales de la Cd. de México, Cancún, Guadalajara, Tijuana, Monterrey, Los Cabos, Puerto Vallarta, Guanajuato, Mérida y Culiacán. Los resultados obtenidos demuestran que en todos los aeropuertos se recomienda implementar estrategias para incrementar su desempeño económico. La peculiaridad del estudio reside en obtener la eficiencia económica fortalecida con bootstrap para esta industria particularmente en México, ya que no existen estudios con estas características específicas.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2023-1621; Aeropuertos; Norteamérica; Eficiencia económica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16782